LENGTH-WEIGHT RELATIONSHIP OF FRESHWATER MUSSEL (Etheria elliptica) FROM RIVER OGBESE, NIGERIA - OYEWOLE, O. O.; ABODERIN, O. O.; ALUKO, O. J.; JADEYEMO, J. O. (Nigerian Journal of Fisheries, 2013)
One hundred mussels (Etheria elliptica) were collected from River Ogbese in Ondo State, Nigeria to determine the Length Weight Relationships (LWR). Sample collections were done fortnightly for a period of three months between August and October 2010 (wet season) and between October and December 2011 (dry season).Each sample was weighed and mantle length measured and recorded. Analysis of the LWR of E. elliptica showed that there is a strong positive relationship between length and weight of samples collected in both seasons. A non-isometric growth was observed in the collected samples, thus indicating an allometric condition factor in E. elliptica